The representation of anger in the elderly characters of Menander's comedy (Circe de clásicos y modernos, 2023)
The work intends to analyze the representation of anger in Menandro's comedy and, in particular, the operation of ‘typification’ of anger in his work, which is linked to the construction of type-characters. We adopt as a theoretical framework some guidelines of the Aristotelian conception of the passions and of social constructivism. In this framework, we maintain that anger in Menander's comedy is traversed by determinations of age, gender and free or slave condition and is presented, above all, as a dominant negative trait of the elderly male citizen and head of the home.
Keywords: passions; anger; character; senex iratus; typification